2010
DOI: 10.1002/ajh.21732
|View full text |Cite
|
Sign up to set email alerts
|

Normal ranges of angiogenesis regulatory proteins in human platelets

Abstract: Platelets sequester angiogenesis regulatory proteins early in tumor growth, which suggests a new avenue for monitoring disease. To date, there are no clinically relevant reference ranges for markers of early angiogenesis. We introduce a new ELISA-based method for accurate and reproducible measurement of vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), platelet factor 4 (PF4), thrombospondin-1 (TSP-1), fibroblast growth factor, basic (bFGF), and endostatin in platelets. To facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 32 publications
3
105
1
2
Order By: Relevance
“…It is well-established that platelets carry a multitude of angiogenesis regulatory proteins in their granules, and the normal ranges of angiogenesis regulators have been characterized in human platelets and in the platelets of patients with malignancy (Peterson et al, 2010).…”
Section: Haematologic Parameters In Metastatic Colorectal Cancer Patimentioning
confidence: 99%
“…It is well-established that platelets carry a multitude of angiogenesis regulatory proteins in their granules, and the normal ranges of angiogenesis regulators have been characterized in human platelets and in the platelets of patients with malignancy (Peterson et al, 2010).…”
Section: Haematologic Parameters In Metastatic Colorectal Cancer Patimentioning
confidence: 99%
“…It is well-established that platelets carry a multitude of angiogenesis regulatory proteins in their ␣ granules, and the normal ranges of angiogenesis regulators have been characterized in human platelets and in the platelets of patients with malignancy. 17 Our laboratory has shown that platelets store angiogenic factors in distinct ␣ granules and that these granules can be differentially released in the presence of the thrombin agonists; with PAR1 resulting in the release of VEGF and PAR4 resulting in release of endostatin. 18 Others have shown that differential release is not limited to angiogenic factors and also affects known hemostatic factors.…”
Section: Introductionmentioning
confidence: 99%
“…9 Platelet depletion in tumor-bearing mice triggers intratumor hemorrhage which is rescued by platelet secretome, 1 demonstrating a requirement for platelet secretion to stabilize angiogenesis in tumor metastases. Indeed, platelet a-granules contain large reservoirs of cytokines and growth factors, including transforming growth factor b (TGF-b) and vascular endothelial growth factor (VEGF), 10,11 which are selectively released upon platelet activation. 12,13 Consistent with a role of platelet secretion in tumor metastasis, TGF-b derived from platelet a-granules has been shown to profoundly impact tumor metastasis and survival by enhancing an epithelial mesenchymal-like transition and suppressing tumor cell natural killer-mediated lysis, respectively.…”
Section: Introductionmentioning
confidence: 99%